2010
DOI: 10.1177/0886260510370595
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Scenarios That May Provoke Acts of Conflict and Aggression Among the General Public: An Exploratory Study

Abstract: The purpose of this article is to use empirical research and theory to investigate the context that may provoke individuals to engage in acts of conflict and aggression. A random sample of the general public from a midsouthern state was surveyed to explore this inquiry. Respondents were asked to indicate their level of reaction to a number of situations that often lead people to engage in conflict and/or aggression with other people. Several sociodemographic factors served as control variables in the study. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Further developments of the FOE could include, e.g., a shorter time limit to decide and/or additional tradeoffs for fight and avoid decisions. Such constraints would better recreate real world aggression episodes, in which responses to provocation are likely adopted after one-shot, impulsive decisions (Lowe and May, 2011; Simons et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Further developments of the FOE could include, e.g., a shorter time limit to decide and/or additional tradeoffs for fight and avoid decisions. Such constraints would better recreate real world aggression episodes, in which responses to provocation are likely adopted after one-shot, impulsive decisions (Lowe and May, 2011; Simons et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…However, this study only focused on high school students and does not take into consideration other life stressors that occur after high school. In general, they noted that males are more likely to be reactive to strain than females (Lowe and May 2011).…”
Section: Gendermentioning
confidence: 99%
“…The moderated models indicated that while females were not inclined to physically respond to strain in one way or another, they were likely to experience both negative emotion sets, keeping in line with the "overly emotional" results found in the mediated models. These differences are interesting, but Lowe and May's (2011) research indicated that in high school students, males and females reacted to strain equally, so that may explain why these differences exist. The females may have lashed out in deviance due to pressures to perform well in school because they see it as the only pathway to economic success/stability and they do not want to let their family/peers down.…”
Section: Figure 13 Financial Strain Mediated Path Modelmentioning
confidence: 99%